(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The Claisen-Schmidt condensation of 4-(aryl)-aminobenzaldehyde and 2-hydroxyacetophenone resulted in a new series of heterocyclic chalcone (4a-4g) derivatives. Nucleophilic aromatic substitution (SNAr) of 4-fluorobenzaldehyde with heterocycle amines by ultrasonication in the presence of a base and polar aprotic solvent yielded 4-(aryl)-aminobenzaldehydes. Spectral investigations were used to establish the structures of synthesized compounds. The in vitro anti-cancer activity of the synthesized derivative was evaluated against MCF-7 (breast cancer) cells by SRB assay. Compounds 4c, 4b, and 4c have a high affinity for the ER receptor binding site, whereas compounds 4c and 4g have a moderate affinity for the VEGER-2 receptor. The GI50 value of 4c ((E)-1-(2-hydroxyphenyl)-3-(4-(4-methylpiperazin-1-yl)-phenyl) prop-2-en-1-one) was 44.6 uM, while the GI50 value of all other derivatives was greater than 80 uM. These findings lay the groundwork for additional research into the combination's potential uses in cancer therapy.